BIAS GENDER DALAM SASTRA ANAK: STUDI PADA BUKU KECIL-KECIL PUNYA KARYA - Umami, Rizka Hidayatul (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2018)
Literary works are divided into several types, some of which are included in children's literature and some are included in the category of adult literature. The fundamental difference between these two works is the content and segmentation of the reader. The purpose of children's literature, in general, is an entertainment and media for them to learn and develop their interest in writing. Please note that children's literature has two broad lines based on the author. There are children's literary works that are made by children and for children to read as well. There is more children's literature created by adults. Good literature, in the sense of literary works that have learning value, must contain gender-sensitive values. The meaning of gender-sensitive is that children learn as early as possible to respect each other even if they come from other genders. What the child reads will be one of the factors causing the development of the child's identity. Therefore, as far as possible, children must be given an early understanding and understanding regarding gender sensitive children's literature. For this reason, this study then discusses the work of children's literature that has been published. Only a few samples were skinned to find out to what extent, children's literature was able to tolerate the existence of other types of gender that also coexisted in society.